Spiritualitas Islam dan Gerakan Politik Ingkar NKRI (Studi terhadap Gerakan Politik HT di Indonesia) - Zusiana Elly Elly Triantini (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
The presence of Reformation Order in Indonesia bears new Islamic spirituality in various forms,and one of them is the born of Hizbut Tahrir Indonesia (HTI) which represents Hizbut Tahrir (HT) in the Middle East. The members claim that HTI is an ideological political party which is based on Islamic doctrines and its dakwa is based on the obligation to uphold khila>fah Isla>miyah supported by fikrah (idea) as a means for change. This group has issued some controversial fruits of ijtihads on politics which lead to pro and con among the debate on the discourse of upholding democracy in Indonesia. They reject historical interpretation. If they admit explanation on when,where and background of quranic verses, they will stop on textual understanding. Eventssurrounding the revelation of verses are only understood as historical background which should be adopted and duplicated into our modern live. The verse cannot be interpreted outof the text. There is no critique on previous understandings. They interpret the text anddisregard previous interpretation. These paper is presented simply affirms that new islamic spirituality in Indonesia has many influences to NKRI.